2014
DOI: 10.3390/vetsci1030159
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Metabolism of Lomustine in Dogs and Comparative Cytotoxicity of Lomustine and Its Major Metabolites in Canine Cells

Abstract: Abstract:The nitrosourea drug lomustine is used clinically for treating a wide variety of malignancies, most commonly brain tumors and lymphoma. Lomustine undergoes hydrolysis in vivo to form isomeric metabolites, primarily trans-4-hydroxylomustine (trans-4) and cis-4-hydroxylomustine (cis-4) in various animal species including humans. Despite its widespread usage to treat canine lymphoma, the metabolism of lomustine has not been studied in dogs. It is reported that 4'-hydroxylation products of lomustine (tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In our previous study, we have shown that lomustine and its metabolites showed a time and concentration dependent toxicity in canine lymphoma cell lines 17–71 and GL-1 [ 22 ]. However the canine hepatocytes did not show any detectable cell killing even 6 days after exposure to the drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we have shown that lomustine and its metabolites showed a time and concentration dependent toxicity in canine lymphoma cell lines 17–71 and GL-1 [ 22 ]. However the canine hepatocytes did not show any detectable cell killing even 6 days after exposure to the drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In our previously published cytotoxicity study [ 22 ], lomustine and its metabolites showed similar degree of cell killing in the canine lymphoid cell lines 17–71 and GL-1, and canine hepatocytes. As alkylation is thought to be the main reason for the cytotoxic effects of these drugs [ 3 ], we wanted to investigate if the compounds have similar pattern of alkylation.…”
Section: Introductionmentioning
confidence: 87%
“…In one study, T-cell lymphomas actually showed a higher degree of intrinsic drug resistance than B-cell lymphomas (Zandvliet et al, 2015). On the other hand, it is known that alkylating agents are not a substrate of P-glycoprotein efflux mechanisms, and cross resistance is uncommon (Teicher et al, 1986;Borst 2012;Chakkath et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[15] PAC-1 and its derivatives induce apoptosis and are cytotoxic in cell culture to a diverse array of cancer cells, including cell lines derived from white blood cell cancers (lymphoma, [15, 4251] leukemia, [15, 24, 44, 4850, 5255] and multiple myeloma [24, 55]), diverse carcinomas (breast, [15, 44, 48, 49, 5254, 5659] renal, [15] adrenal, [15, 6062] colon, [15, 48, 55, 5759, 63] lung, [15, 48, 49, 5259, 6367] cervical, [44, 55] gastric, [48, 49, 55, 57, 58, 63] ovarian, [55] liver, [48, 49, 55] prostate, [48, 49] and gallbladder [48, 49]), and other solid tumor types (melanoma, [15, 44, 48, 49] osteosarcoma, [55] neuroblastoma, [15, 55, 57, 58] and glioblastoma [48, 49, 68]). Patient-derived samples from colon cancer [15], chronic lymphocytic leukemia [23], and multiple myeloma [24] are also sensitive to PAC-1 and derivatives, and a therapeutic effect has been demonstrated in multiple murine tumor models [15, 48, 49, 56, 65, 66, 69] and in pet dogs with cancer.…”
Section: Pac-1mentioning
confidence: 99%
“…This depletion of the labile zinc pool restores procaspase-3 enzymatic activity, allowing for cleavage of procaspase-3 to caspase-3 and the initiation of the execution pathway of apoptosis. [42] PAC-1 is now widely used as a tool compound for the induction of apoptosis [51, 59, 67, 68, 82, 83], and for the direct activation of procaspase-3 downstream of the mitochondria. [8487] In addition, multiple independent studies have confirmed the direct procaspase-3 activation mechanism, [48, 85, 88] for example in detailed studies with selective caspase inhibitors, [85] selective caspase substrates, [48] and in Bax/Bak double knockout cells.…”
Section: Pac-1mentioning
confidence: 99%